The Drosophila Receptor Tyrosine Kinase Alk Constrains Long-Term Memory Formation. - Gouzi, J.Y.; Bouraimi, M.; Roussou, I.G.; Moressis, A.; Skoulakis, E.M.C. (Journal of Neuroscience, 2018)
In addition to mechanisms promoting protein-synthesis-dependent long-term memory (PSD-LTM), the process appears to also be specifically constrained. We present evidence that the highly conserved receptor tyrosine kinase dAlk is a novel PSD-LTM attenuator in Drosophila Reduction of dAlk levels in adult ?/? mushroom body (MB) neurons during conditioning elevates LTM, whereas its overexpression impairs it. Unlike other memory suppressor proteins and miRNAs, dAlk within the MBs constrains PSD-LTM specifically but constrains learning outside the MBs as previously shown. Dendritic dAlk levels rise rapidly in MB neurons upon conditioning, a process apparently controlled by the 3'UTR of its mRNA, and interruption of the 3'UTR leads to enhanced LTM. Because its activating ligand Jeb is dispensable for LTM attenuation, we propose that postconditioning elevation of dAlk within ?/? dendrites results in its autoactivation and constrains formation of the energy costly PSD-LTM, acting as a novel memory filter.SIGNIFICANCE STATEMENT In addition to the widely studied molecular mechanisms promoting protein-synthesis-dependent long-term memory (PSD-LTM), recent discoveries indicate that the process is also specifically constrained. We describe a role in PSD-LTM constraint for the first receptor tyrosine kinase (RTK) involved in olfactory memory in Drosophila Unlike other memory suppressor proteins and miRNAs, dAlk limits specifically PSD-LTM formation as it does not affect 3 h, or anesthesia-resistant memory. Significantly, we show conditioning-dependent dAlk elevation within the mushroom body dendrites and propose that its local abundance may activate its kinase activity, to mediate imposition of PSD-LTM constraints through yet unknown mechanisms.